2017
DOI: 10.1177/2473011417s000268
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Moderate Hallux Valgus by Percutaneous, Extra-articular Reverse-l Chevron (PERC) Osteotomy

Abstract: The purpose of this study was to report a single surgeon series of consecutive patients with moderate hallux valgus managed with a Percutaneous Extra-articular Reverse-L Chevron (PERC) osteotomy. Methods: A total of 38 patients underwent 45 PERC procedures. A medial approach is used just proximal to the flare of the metatarsal head. The osteotomy is performed using a burr, the thickness of which is selected according to the planned correction and shortening. A second dorsolateral approach is then performed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…This study included a wide range of hallux valgus deformities, with >25% categorized as “severe” preoperatively. The mean preoperative IMA and HVA and postoperative deformity correction in this study were greater than or comparable with those in other series 8-10,12-16,29,30 (Table VI). This supports the view that MICA can be used to treat a wide range of deformity severity.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This study included a wide range of hallux valgus deformities, with >25% categorized as “severe” preoperatively. The mean preoperative IMA and HVA and postoperative deformity correction in this study were greater than or comparable with those in other series 8-10,12-16,29,30 (Table VI). This supports the view that MICA can be used to treat a wide range of deformity severity.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies of third-generation MIS have demonstrated improved clinical and radiographic outcomes for a wide range of hallux valgus deformities 8-16 . These studies are limited in number and consist of case series with small sample sizes, short follow-up, unvalidated outcomes, inconsistent techniques, and a high risk of bias.…”
mentioning
confidence: 99%
“…13 These 3G MIS techniques include the percutaneous, extra-articular reverse-L chevron (PERC) osteotomy and the MICA osteotomy as described by Vernois and Redfern. 27,42 Encouraging results of the MICA technique have been reported with regard to outcome scores and radiographic parameters. In a series of 40 MICA cases, Holme et al 17 reported improvement in AOFAS scores from 48 to 93, HVA from 32 to 12 degrees, and IMA from 13 to 7 degrees.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 14 A satisfaction rate higher than 90% was reported in 2 studies. 23 , 27 In addition, the satisfaction rate was higher than 80% in 3 studies, and in 2 studies the satisfaction rate was higher in the MIS group vs open surgery ( Table 3 ). 16 , 20 , 35 Cosmesis was shown to be better in the MIS group compared to the open group.…”
Section: Resultsmentioning
confidence: 96%
“…A total of 7 studies included a satisfaction rate in their data, and all of them reported a >80% rate of satisfaction among their patients. 3 , 14 , 16 , 20 , 23 , 27 , 35 There were 3 studies that reported a satisfaction rate of >95% among their patients. 3 , 14 , 23 …”
Section: Discussionmentioning
confidence: 99%